The Influence of Service Quality and Location on Fuel Purchase Decisions at COCO Gas Stations 11.201.107 Hm. Yamin Medan - Setiawan, Reza; Tasya, Khalisa Aulia; Apriani, Wulan; Zetira, Cinthia Tasyva; Hasyim, Hasyim (Formosa Journal of Applied Sciences, 2024)
This research tries to ascertain how service quality influences fuel purchasing decisions at SPBU Coco 11.201.107 HM. Yamin Medan. This research uses explanatory research which uses descriptive statistical methods to verify whether there is an influence between the services provided on customers' fuel purchasing decisions. The research results showed that respondents' responses regarding the quality of service were considered good. Respondents rated the services and facilities provided at the Coco HM gas station positively. Yamin. Similar research can be carried out between regions for the next stage of the research process in the same environment with different characteristics and with changes in research variables that can be developed for further research.